2003
DOI: 10.1002/chi.752
|View full text |Cite
|
Sign up to set email alerts
|

Promoting children's interest in health: an evaluation of the child health profile

Abstract: The child health profile was developed as an extension for older children of the personal child health record, which has normally been kept by mothers. The profile was introduced in three health board areas in Scotland. A questionnaire survey of young people revealed a mixed response concerning the usage and value of the profile. A small number had used it fully as a means of recording or communicating about personal health-related matters, but a majority had not actively used the profile and two fifths said t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Researchers must acknowledge participants' support and willingness to participate in research activities. Hill and Morton (2003) also state that if children are not committed to taking part in research, for whatever reason, they are likely to give a negative response and not engage at all with the question. As a result, it offers a practical justification for making sure that the children taking part in the research have agreed to it in order for the research to proceed.…”
Section: Recognition Of Children's Opinionsmentioning
confidence: 99%
“…Researchers must acknowledge participants' support and willingness to participate in research activities. Hill and Morton (2003) also state that if children are not committed to taking part in research, for whatever reason, they are likely to give a negative response and not engage at all with the question. As a result, it offers a practical justification for making sure that the children taking part in the research have agreed to it in order for the research to proceed.…”
Section: Recognition Of Children's Opinionsmentioning
confidence: 99%
“…Clearly, while the majority of children would recommend the survey to a friend, we need to ensure that we do not ask questions of children that are too lengthy . Research has shown that if children are not committed to taking part in a survey, for whatever reason, they are likely to give negative responses, or not engage at all with the questions (Morrow 2000;Hill & Morton 2003) . This provides another more pragmatic reason for ensuring that children do give their informed consent to take part in the survey .…”
Section: Voluntary Informed Consentmentioning
confidence: 99%